Algunas propuestas para la reforma constitucional del Senado - Alonso de Antonio, José Antonio (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
As the Spanish autonomy system has been consolidated, the Senate must serve as an authentic Chamber of Territorial Representation. Thus, the Spanish Constitution must be reformed with regard to the composition and functions of that Chamber. In this sense, it seems opportune to augment the number of Senators designated by the Autonomous Communities, as an adaptation of the Senate’s present subordination to the Congress of Deputies with regard to legislative procedures, and the increase of the Senate’s autonomous functions.